Application of flywheel energy storage for heavy haul locomotives. (1st November 2015) - Spiryagin, Maksym; Wolfs, Peter; Szanto, Frank; Sun, Yan Quan; Cole, Colin; Nielsen, Dwayne
Highlights: A novel design for heavy haul locomotive equipped with a flywheel energy storage system is proposed. The integrated intelligent traction control system was developed. A flywheel energy storage system has been tested through a simulation process. The developed hybrid system was verified using an existing heavy haul railway route. Fuel efficiency analysis confirms advantages of the hybrid design. Abstract: At the present time, trains in heavy haul operations are typically hauled by several diesel-electric locomotives coupled in a multiple unit. This paper studies the case of a typical consist of three Co–Co diesel-electric locomotives, and considers replacing one unit with an alternative version, with the same design parameters, except that the diesel-electric plant is replaced with flywheel energy storage equipment. The intelligent traction and energy control system installed in this unit is integrated into the multiple-unit control to allow redistribution of the power between all units. In order to verify the proposed design, a three-stage investigation has been performed as described in this paper. The initial stage studies a possible configuration of the flywheel energy storage system by detailed modelling of the proposed intelligent traction and energy control system. The second stage includes the investigation and estimation of possible energy flows using a longitudinal train dynamics simulation. The final stage compares the conventional and the proposed locomotive configurations considering two parameters: fuel efficiency and emissions reduction.